Think Indigenous : Native American spirituality for a modern world - Good Feather, Doug; Pineda, Doug Red Hail (Carlsbad, California : Hay House, Inc., 2021)
"With each generation, we have drifted further and further away from our ability to recognize and connect with the source of our original design. In this modern world, we spend our attention in ways that benefit the powers that be, and not ourselves or the earth. But what if we called upon the knowledge of our roots to move us forward, individually and collectively as a society? Direct descendant of Grandpa Chief Sitting Bull and American Lakota spiritual leader Doug Good Feather will guide you to becoming grounded with your own indigenous roots and your innate ancestral knowing that all beings are divinely connected"--.
Keywords: Lakota philosophy; Lakota Indians -- Religion; Spirituality